Influence of social and economic development on water quality in Dongting Lake - Yu Feng (Elsevier, 2021)
Lakes have faced the challenge of alleviating water deterioration due to rapid socioeconomic development. This fact highlights the urgency to understand the impact of socioeconomic development on water quality. Although existing studies have devoted efforts on the research of the relationship between socioeconomic development and water quality, the theoretical basis and process of factors selection (socioeconomic factors and water quality factors) have often been ignored. A conceptual model was employed in this work to select the candidate indicators. Meanwhile, a new developed method that introduces a monthly correction coefficient was proposed to evaluate socioeconomic indicators and seasonal-trend decomposition (STL) using the locally weighted scatterplot smoothing (LOESS) method. At the same time, the steady-state transformation index (RSI) were adopted to further select water quality indicators. Base on that, canonical correlation analysis (CCA) and the measured and ideal values of water quality indicators were used to quantitatively study the degree of influence of socioeconomic systems and their key factors on water quality. The proposed methodology were applied to the Dongting Lake basin and its four sub-watersheds, the Xiang, Zi, Yuan and Li River watersheds, as these water bodies have been seriously affected by human activities in recent years. The results showed that there was a high correlation between the socioeconomic system and water quality, with significant temporal and spatial characteristics. The average annual impact degree of the socioeconomic system on water quality was at a moderate level for Dongting Lake basin and its four sub-watersheds, while the impact degree for Xiang River watershed was higher than that of the other watersheds. The influence degree decreased in the Dongting Lake basin, Xiang River and Li River watersheds, whereas the trend was the opposite in the Yuan River and Zi River watersheds from 2004 to 2017. Water consumption (WC), percentage of cultivated land area (CA), total nitrogen (TN) input from agricultural non-point sources (A_TN), and human response factors, such as industrial wastewater compliance discharge rate (WR) and sewage treatment (ST), were the main socioeconomic factors affecting the water quality of Dongting Lake. Implementation of an efficient water use plan, controlling the agricultural non-point source pollution and improving the sewage treatment capacity should be given priority in order to effectively improve the water quality of Dongting Lake. The present study showed the relationship between socioeconomic drivers and water quality, and provided a reliable tool for decision makers in watershed management.